STRATEGI DIGITAL BRANDING UNIVERSITAS KRISTEN INDONESIA MALUKU (UKIM) DALAM MEMBANGUN CITRA INSTITUSI PENDIDIKAN TINGGI SWASTA DI MALUKU - Silvia Leuwol; Rido Latuheru (Jurnal Administrasi Terapan, 2026)
The digital transformation era has changed how higher education institutions communicate with the public. Christian University of Indonesia Maluku (UKIM) as a private higher education institution in Eastern Indonesia faces challenges in building a strong institutional image through digital branding strategy. This research aims to analyze the digital branding strategy implemented by UKIM in building institutional image. This research uses a qualitative descriptive approach with data collection techniques through semi-structured interviews, observation, and documentation. Research informants include the Rector, Vice Rector III, and Vice Rector IV. The results show that UKIM has implemented a digital branding strategy through an official website, UKIM TV YouTube, social media, and local media publications. Content strategy focuses on institutional activity documentation and promotion of the 'Campus of Brothers' value which reflects inclusivity and tolerance. However, implementation still faces significant challenges including limited human resources, infrastructure, inter-unit coordination, budget constraints, and mindset change. Achievements reached are evident from increased digital visibility, external recognition, and strengthened institutional image. Research recommends establishing a special digital branding unit, improving inter-unit coordination, infrastructure investment, and organizational culture transformation focused on digitalization to increase the effectiveness of UKIM's digital branding strategy.Keywords: digital branding, institutional image, communication strategy, higher education, digital transformation.